(untitled) (Journal of Contemporary Studies, 2025)
This article delves into the potential of utilizing Soft Power as a tool to address extremism within the youth population of Pakistan. It explores how leveraging Soft Power can help diminish the allure of ideologies by influencing attitudes, values, and behaviors through cultural, educational, and informational initiatives. The study show cases how effective soft power can be in encouraging inclusivity, tolerance, and civic participation among Pakistanis. Furthermore, it discusses the roles that various stakeholders—such as allies, civil society groups, and governmental bodies—can play in utilizing power to tackle the underlying factors contributing to extremism. Ultimately, it underscores the importance of implementing a power strategy in nurturing peace, stability, and resilience among Pakistani youth.